Tinjauan Kriminologis Terhadap Kasus Pembunuhan Balita Oleh Remaja 15 Tahun di Sawah Besar : Faktor Pemicu, Dinamika Psikologis, dan Implikasi Kebijakan Kriminal - Aryaputri, Aqila Shafiqa; Ikhsan, Muhamad Hiroshi; Puspadewi, Gladys Trias; Siregar, Tiara Rebecca Kezia; Cahyanto, Anastasya Regina Sekar; Yuli, Yuliana (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The case of the murder of a toddler by a 15 year old teenager in Sawah Besar has spread widely among Indonesian society. The purpose of this article is to conduct a criminological review of the case with a focus on three aspects, namely the triggering factors, the psychological dynamics of the perpetrator, and the implications for criminal policy. Factors that trigger murder are studied by analyzing the background of the perpetrator and victim, as well as the socio-economic conditions of the surrounding environment. The perpetrator's psychological dynamics are analyzed using psychological theories to understand his motives and thought processes. The implications of criminal policy are explored by examining the effectiveness of the juvenile criminal justice system and alternative remedies. Based on the analysis found, it shows that there is a combination of factors that trigger murder, such as the perpetrator's background having experienced traumatic experiences, growing up in a troubled family, and frequently seeing violence. There is also the condition of the victim who is a child who is vulnerable and easily attacked, meaning he does not dare to fight back. Also, there are factors from the surrounding environment due to lack of supervision from parents and social control. Psychological analysis shows that the perpetrator may have mental disorders and psychopathology that need to be treated professionally. A review of criminal policy shows that the juvenile criminal justice system needs to be reviewed to ensure a balance between justice and rehabilitation. Other options regarding management such as prevention and early intervention programs also need to be considered.